‘Balik Kampong’: is Malaysia facing the trends of de-urbanization? - Nur Huzeima Mohd Hussain,; Byrd, Hugh (Institut Alam dan Tamadun Melayu, UKM, 2016)
Malaysia is a fast-grown developing country which took only 30 years to shift from predominantly agriculture-based to manufactured-dependent society. This kampong to urban migration has created a new generation of urban society who had disconnected themselves from the traditional subsistence farming but kept maintaining an occasional connection with their hometown. With new jobs, environment and lifestyle, these urban migrants’ life and livelihood in cities improved and expanded. Growth in urban population and affluence raised the demand for housing, food and technological goods. With increased growth in demand, came an increased challenge in resource management to satisfy needs. A recent debate has highlighted issues on oil depletion and competition from neighboring countries that indicates a possible economic decline. This situation has triggered discussions about limits to urbanization and the possibility of urban and peri-urban food production in order to re-localize urban areas. Therefore, there is an emerging of decentralization of cities and population in Malaysia. This paper questions whether there is a further progression towards ‘de-urbanization’ or a return to a new form of rural life that takes advantage of new technologies to assists new way of life and improves the standard of living in kampong.